Neoadjuvant Dose-Dense Methotrexate, Vinblastine, Doxorubicin, and Cisplatin With Pegfilgrastim Support in Muscle-Invasive Urothelial Cancer: Pathologic, Radiologic, and Biomarker Correlates - Choueiri, Toni K.; Jacobus, Susanna; Bellmunt, Joaquim; Qu, Angela; Appleman, Leonard J.; Tretter, Christopher; Bubley, Glenn J.; Stack, Edward C.; Signoretti, Sabina; Walsh, Meghara; Steele, Graeme; Hirsch, Michelle; et al. (Journal of clinical oncology, 2014)
In advanced urothelial cancer, treatment with dose-dense methotrexate, vinblastine, doxorubicin, and cisplatin (ddMVAC) results in a high response rate, less toxicity, and few dosing delays. We explored the efficacy and safety of neoadjuvant ddMVAC with pegfilgrastim support in muscle-invasive urothelial cancer (MIUC). Patients with cT2-cT4, N0-1, M0 MIUC were enrolled. Four cycles of ddMVAC were administered, followed by radical cystectomy. The primary end point was pathologic response (PaR) defined by pathologic downstaging to ≤ pT1N0M0. The study used Simon's optimal two-stage design to evaluate null and alternative hypotheses of PaR rate of 35% versus 55%. Secondary end points included toxicity, disease-free survival (DFS), radiologic response (RaR), and biomarker correlates, including ERCC1. Between December 2008 and April 2012, 39 patients (cT2N0, 33%; cT3N0, 18%; cT4N0, 3%; cT2-4N1, 43%; unspecified, 3%) were enrolled. Median follow-up was 2 years. Overall, 49% (80% CI, 38 to 61) achieved PaR of ≤ pT1N0M0, and we concluded this regimen was effective. High-grade (grade ≥ 3) toxicities were observed in 10% of patients, with no neutropenic fevers or treatment-related death. One-year DFS was 89% versus 67% for patients who achieved PaR compared with those who did not (hazard ratio [HR], 2.6; 95% CI, 0.8 to 8.1; P = .08) and 86% versus 62% for patients who achieved RaR compared with those who did not (HR, 4.1; 95% CI, 1.3 to 12.5; P = .009). We found no association between serum tumor markers or ERCC1 expression with response or survival. In patients with MIUC, neoadjuvant ddMVAC was well tolerated and resulted in significant pathologic and radiologic downstaging.